(untitled) (Jurnal Bina Praja, 2017)
Globalization requires Small and Medium enterprises to increase its existence in order to compete in a global world. Small and Medium enterprises have to always increase the creativity to be able to create products that have innovated. Yet currently, SMEs still have obstacles in increasing its existence, such as the poor ability of businesses, the difficulty of access to capital and does not quickly follow the development of science and technology. The purpose of this study is to determine the role of government to grow the performance of SMEs towards creative industry in Jambi Province. The sampling technique for the location and respondents is in a purposive sampling. The provision of sample site and respondents selection is based on the already defined criteria. For locations, there are 7 (seven) locations selected as the samples and 200 for the sample of respondents. The analysis method used is the descriptive analysis depicting government role in improving SMEs performance. The results of the study explain that the government’s support is still low to improve the quality of human resources through education and training. There are still SMEs which have never attended the training because the Department of Industry and Trade has not had a database of SMEs which have attended the training or not. SMEs still have capital problems. The government is not yet optimally introducing technological advances and not yet optimally assisting the development and marketing of products. There is overlapping of the same programs among SKPD that empower SMEs. From the other side, the business climate is already conducive as the government gives ease of permit and smoothness of business. The results of the study recommend (1) to provide education and training equally for SMEs (2) Creation of synergistic between the related SKPD and SMEs (3) Developing microfinance institution to solve the capital problem (3) Jambi Provincial Government needs to build cooperation with universities to do Transfer of science and technology.